Implementation of WASH in Schools (WinS) Program in the New Normal - Kalid T. Udto (PT FORMOSA CENDEKIA GLOBAL, 2022)
This study aimed to evaluate the status of the implementation of WASH in Schools (WinS) Program in Parang North District of Maguindanao II Division. The study used a descriptive-method of research design to describe the status of the implementation of the program. Fifty-six members of the Technical Working Groups (TWG) in the seven schools were used as respondents while survey questionnaire and interview were used as research instruments. The study found that proper execution of school-based management approach had a great impact in the implementation of the WASH in Schools (WINS) program. The continuous capacity building and technical assistance of program implementers contributed to an organized, efficient and effective mechanism of program implementation. Furthermore, the parents and community played a vital role in the successful implementation of the program, hence the schools should strengthen their partnership with these stakeholders in order to collaboratively develop and improve the program which is beneficial in ensuring that learners are safe and healthy especially in the new normal.